2005
DOI: 10.1016/j.jcis.2004.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on thermocapillary drop migration at large Marangoni number in reduced gravity

Abstract: Results from a space experiment on thermocapillary drop migration conducted on board the Chinese spacecraft ShenZhou-4 are presented in this paper. In the experiment, isolated drops of Fluorinert liquid moved in a matrix liquid of 5cst silicone oil at values of the Marangoni numbers (Ma) ranging up to 5500 and the interferometry images showed the temperature distribution inside the test cell. The drop migration velocity was measured. The experimental results show that the scaled drop migration velocity V/V(YGB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 11 publications
3
54
0
Order By: Relevance
“…Both the theoretical analysis and numerical simulation are based on the assumptions of quasi-steady state and non-deformation of the droplet. However, the experimental results of Hadland et al [11] and Xie et al [28] were not in qualitative agreement with the above theoretical and numerical results, and it was shown that the droplet migration speed non-dimensionalized by the YGB velocity decreased as Ma number increased. The experiment investigation was completed in several ranges of large Ma numbers, where the droplet migration was in an accelerating state and did not reach a steady one.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Both the theoretical analysis and numerical simulation are based on the assumptions of quasi-steady state and non-deformation of the droplet. However, the experimental results of Hadland et al [11] and Xie et al [28] were not in qualitative agreement with the above theoretical and numerical results, and it was shown that the droplet migration speed non-dimensionalized by the YGB velocity decreased as Ma number increased. The experiment investigation was completed in several ranges of large Ma numbers, where the droplet migration was in an accelerating state and did not reach a steady one.…”
Section: Introductionmentioning
confidence: 77%
“…In the following calculations, we adopt the silicone oil of nominal viscosity 5cst and the FC-75 Fluorinert liquid, i.e., the working media in the space experiment [28], as the continuous phase fluid and the droplet, respectively. The physical parameters of the continuous fluid and the droplet at temperature 25 • C are given in Table 1.…”
Section: Results and Analysismentioning
confidence: 99%
“…On the fourth Shen-Zhou spaceship, Xie et al carried out experiments with larger values of Re 1 ͑up to 300͒ and Ma 1 ͑up to 5500͒. 11 There are also lots of numerical studies on this subject. Szymczyk and Siekmann 12 first calculated the steady migration of bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the years of ground-based research of the drop or bubble migration by means of matched-density and the facility of drop shaft [30,31] , the space experiment of drop thermocapillary migration at large Ma was performed on board the space ship Shen Zhou (SZ-4) of China in 2002 [32] . The experimental apparatus consisted of a test cell unit including drop injection system, optical diagnostics and illumination system, a recorder for data and video image recording, a controller unit and a power supply, as shown in Figure 5.…”
Section: Experiments Of Drop Marangoni Migrationmentioning
confidence: 99%